The feedback dilemma: Aligning L2 writing instruction with student preferences - Sabariah Abd Rahim; Alice Alim; Cui Qiuxiang; Yang Xiangxian (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
In writing classes, teachers implement Written Corrective Feedback (WCF) as a form of Corrective Feedback (CF). It is an instructional strategy teachers used in the classroom to improve L2 students' writing skills. Nevertheless, the incongruity between the preferences of students and the instructional strategies employed by teachers for WCF has resulted in challenges for teachers and perplexity for the students. The study aims to achieve the following objectives: 1) to examine the forms of CF used by L2 teachers when assessing students' writing, 2) to explore the types of CF that students prefer when receiving feedback on their writing, and 3) to determine whether the teachers' WCF practices align with the students' preferences. The researchers employed the Feedback Scale to gather data for the study. Additionally, purposive opportunistic sampling was utilised in selecting the study’s participants. The findings show that the L2 teachers provide more indirect WCF and focused WCF, whereas the L2 students prefer direct WCF and unfocused WCF. This demonstrates the concept of a disparity between the pedagogical approaches that teachers employ and the preferences that students have expressed regarding WCF. The study has implications on the writing instruction of English Language writing class.